Interaksi Monyet Ekor Panjang (Macaca fascicularis) dengan Manusia di Pantai Bama Taman Nasional Baluran: Interaction Between Long-Tailed Macaques (Macaca fascicularis) and Humans at Bama Beach, Baluran National Park: An Analysis of Perceptions and Behavioral Observations - Amanda Dwi Nursalamah; Nur Ainna Fairuz Jasmine; Anis Syavira Avivatu Zahra; Hari Sulistiyowati; Retno Wimbaningrum; Rendy Setiawan; Nanang Dwi Wahono; Arif Mohammad Siddiq (Departemen Biologi, Institut Pertanian Bogor, 2026)
Bama Beach is one of the tourism areas in Baluran National Park (BNP), which is also a habitat for long-tailed macaques (Macaca fascicularis). This species is commonly found with aggressive behavior and bravery towards humans at Bama Beach. The aim of this study is to determine the level of interaction that occurs between LTM and humans at Bama Beach, BNP. The method used was a survey questionnaire (Likert scale) and also field observations to support the results of the interaction level in May 2023. Questionnaire data collection is aimed at visitors (64 respondents) and BNP staff (six respondents). While field observations were collected by scan sampling methods during seven days. There are seven categories of interaction that were observed, i.e., proximity, physical contact without being aggressive, taking humans' stuff, intimidating, chasing or lunging, facial or voice threats, and biting or scratching. The results of the questionnaire based on a Likert scale obtained an average index value of 34.25% (mild interaction). The resulting interaction level is supported by the acquisition of the percentage of interaction categories based on field observations, namely the proximity interaction, which has the highest value (44%). Whereas, we also found the threatened interaction to humans, including intimidating (20%), facial or voice threats (16%), taking humans' stuff (14%), and chasing or lunging (5%).